Spatial interaction analytical links study of category M1 road trains - Orysenko, Oleksandr; Skoryk, Maksym; Kryvorot, Anatolii; Virchenko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2022)
During the movement of a road train, the towing device takes on the load from one link of the road train and transmits it to another. In the study of the processes of links interaction in real traffic conditions, a spatial system of forces acts on each road train link and there is a need to bring them to the calculated plane. It is proposed to consider each link in a separate spatial coordinate system, which is fixed with this link, and then, using the developed transition tables, to bring these forces to the coordinate system, which is fixed with another link
Keywords: road train; traction and coupling device; trailer; rotation matrices; fixed and moving coordinate systems